An Estimate of Primary Productivity in Air Hitam Forest Reserve - Kueh, Roland Jui Heng (2000)
Natural forest is a mosaic of structural phases. Different growth stages have different productivity level. The main objective of this study is to estimate the net primary productivity (NPP) of three different growth stages in Air Hitam Forest Reserve by using the summation method. The first study area is a more mature and diverse stand (Biodiversity Plot, BP). The second (Macaranga Plot I, MPI) and third study (Macaranga Plot II, MPII) areas are younger and more homogenous stands. Trees in Diameter Class 10-20 em dominated all the study plots accounting for between 56 and 78 % of all the trees in the plots. The basal area for BP was 21.1 m2/ha, in MPI was 27.9 m2/ha and MPH was 19.7 m2/ha. The most common species in BP was Eugenia griffithii while in MPI and MPH it was Macaranga gigantea. A modified equation was derived from Acacia mangium biomass equations and Kato's et al. (1978) equation. The total biomass estimated was 201.7 t/ha in BP, 273.6 t/ha in MPI and 15l.8 t/ha in MPH. Biomass was estimated over two consecutive occasions. The estimated annual biomass increment (∆Y) was 0.8 t/ha/yr in BP, 1.3 t/ha/yr in MPI and 2.0 t/ha/yr in MPII.